2017
DOI: 10.1158/0008-5472.can-17-0388
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 Inhibition Reverses Mesenchymal Transdifferentiation of Glioma Stem Cells by Regulating C/EBPβ Signaling

Abstract: Necrosis is a hallmark of glioblastoma (GBM) and is responsible for poor prognosis and resistance to conventional therapies. However, the molecular mechanisms underlying necrotic microenvironment-induced malignancy of GBM have not been elucidated. Here, we report that transglutaminase 2 (TGM2) is upregulated in the perinecrotic region of GBM and triggered mesenchymal (MES) transdifferentiation of glioma stem cells (GSC) by regulating master transcription factors (TF), such as C/EBPβ, TAZ, and STAT3. TGM2 expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 47 publications
2
73
1
Order By: Relevance
“…Inhibition of TGM2 decreased survival of tumor cells in an ex vivo organotypic slice model of GBM, and was previously shown to increase survival in a glioma xenograft model. 49 Our findings suggest a new strategy for sensitizing GBM cells to radiotherapy by short-circuiting the normal brain's protective response to radiation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Inhibition of TGM2 decreased survival of tumor cells in an ex vivo organotypic slice model of GBM, and was previously shown to increase survival in a glioma xenograft model. 49 Our findings suggest a new strategy for sensitizing GBM cells to radiotherapy by short-circuiting the normal brain's protective response to radiation.…”
Section: Discussionmentioning
confidence: 80%
“…45 It cross-links fibronectin and has scaffolding functions with integrin β1, both of which are associated with radiation resistance and stemness, 46,47 and has recently been proposed to promote neurogensis from neural stem cells in the adult brain. 48 Its inhibition improved survival in a glioma xenograft model 49 and it has been shown to be a prognostic indicator of shorter time to relapse after chemoradiotherapy. 50 We first confirmed increased expression of TGM2 in matrix from multiple batches of astrocytes from different individuals by western blot (Fig 5B).…”
Section: Irradiated Astrocytes Secrete Tgm2 In Vitro and In Vivo Aftementioning
confidence: 99%
“…TG2 is a cancer stem cell maintenance factor, but this finding suggests that a stem cell marker, ALDH1A3, can also induce TG2 level. C/EBPβ, TAZ, and STAT3 signaling also drives TG2 expression in mesenchymal phenotype cells . This suggests that TG2 is a key protein driving this more aggressive phenotype.…”
Section: Tg2 In Tumor Typesmentioning
confidence: 94%
“…We found that TGase 2 knockdown or TGase 2 inhibition stabilized p53 in RCC, which induced p53-mediated apoptosis because there is less than 4% mutation of p53 in RCC (Kang et al 2016). A recent report showed that TGase 2 is also a key molecular switch of necrosis-induced mesenchymal trans-differentiation by regulating master transcription factors such as C/EBPβ, TAZ, and STAT3 through GADD153 depletion in glioblastoma, which is correlated with recurrent mesenchymal patients and inversely correlated with patient prognosis (Yin et al 2017). Currently, despite the effort of many groups, no small molecule TGase 2 inhibitors are available for clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…GK921 demonstrated RCC regression successfully through p53 stabilization with TGase 2 inhibition although the detail inhibitory mechanism remains to be answered (Ku et al 2014). TGase 2 inhibition using GK921 also blocked mesenchymal trans-differentiation and showed significant therapeutic effect in the mouse glioblastoma model (Yin et al 2017). Therefore, understanding the mechanism of GK921 inhibiting TGase 2 may lead to the development of a new therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%